Co-infecção por vírus dengue, sorotipos 1 e 4, em paciente de cidade de porte médio no Brasil - Colombo, Tatiana Elias [UNESP]; Vedovello, Danila; Mondini, Adriano [UNESP]; Reis, Andrea Francesli Negri; Cury, Amena Alcântara Ferras; Oliveira, Frank Hulder de; Cruz, Lilian Elisa Arão Antonio; Bronzoni, Roberta Vieira de Morais; Nogueira, Maurício Lacerda (FapUNIFESP (SciELO), 2013)
The natural co-infection with dengue virus can occur in highly endemic areas where different serotypes have been observed for many years. We report one case of DENV-1/DENV-4 co-infection in human serum detected by molecular tests. Phylogenetic analysis of the sequences obtained indicated the presence of genotype V and II for DENV-1 and DENV-4, respectively.
Co-infection of dengue virus by serotypes 1 and 4 in patient from medium sized city from Brazil
Keywords: Brazil; Co-infection; Dengue; Flavivirus; capsid protein; nonstructural protein 5; blood analysis; case report; controlled study; dengue; Dengue virus 1; Dengue virus 4; gene sequence; genotype; geographic distribution; human; human cell; male; mixed infection; molecular diagnosis; nucleotide sequence; phylogeny; RNA analysis; serotype; unindexed sequence; virus detection